2013
DOI: 10.1002/grl.50986
|View full text |Cite
|
Sign up to set email alerts
|

In situ observations of supercooled liquid clouds over the Southern Ocean during the HIAPER Pole‐to‐Pole Observation campaigns

Abstract: [1] Clouds over the Southern Ocean exist in a pristine environment that results in unique microphysical properties. However, in situ observations of these clouds are rare, and the dominant precipitation processes are unknown. Uncertainties in their life cycles and radiative properties make them interesting from a weather and climate perspective. Data from the standard cloud physics payload during the High-performance Instrumented Airborne Platform for Environmental Research (HIAPER) Pole-to-Pole Observations g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 27 publications
12
78
0
Order By: Relevance
“…• S in the previous campaign (April 2010) and the subject of Chubb et al (2013), undoubtedly pristine maritime conditions were encountered. Low-level CO concentrations were about 41 ppbv (this may be a seasonal difference compared to HIPPO-4 RF06), but still varied by about 5 ppbv between 5000 and 7000 m a.s.l.…”
Section: Comparison To Clearly Polluted And/or Pristine Casesmentioning
confidence: 89%
See 1 more Smart Citation
“…• S in the previous campaign (April 2010) and the subject of Chubb et al (2013), undoubtedly pristine maritime conditions were encountered. Low-level CO concentrations were about 41 ppbv (this may be a seasonal difference compared to HIPPO-4 RF06), but still varied by about 5 ppbv between 5000 and 7000 m a.s.l.…”
Section: Comparison To Clearly Polluted And/or Pristine Casesmentioning
confidence: 89%
“…Chubb et al (2013) examined two SO flights that encountered low-altitude cloud (i.e. below 2 km) as far south as 67…”
Section: T Chubb Et Al: High Cdnc Observed During Hippo-4mentioning
confidence: 99%
“…would expect that supercooled liquid water might be more prevalent, especially given that Chubb et al (2013) observed it in situ over the Southern Ocean at temperatures as low as 2228C. Huang et al (2012) found in case studies that the DARDAR v1 algorithm often classified cloud tops as ice when CALIPSO classification suggested liquid or unknown, and DARDAR v2 appears to classify more scenes as ice and fewer scenes as SLW compared to v1 (Ceccaldi et al 2013).…”
Section: Cloud Profilesmentioning
confidence: 99%
“…At temperatures greater than about −15 • C, these concentrations remain low: only one particle in every 10 3 or 10 4 will nucleate an ice crystal (Rogers et al, 1998;Chubb et al, 2013;DeMott et al, 2015). However, even when INP concentrations are low at warm subzero temperatures, incloud ice crystal number concentrations (ICNCs) can be orders of magnitude higher (e.g., Hallett and Mossop, 1974;Heymsfield and Willis, 2014;Lasher-Trapp et al, 2016;Taylor et al, 2016;Ladino et al, 2017), particularly in tropical maritime clouds (Koenig, 1963(Koenig, , 1965Hobbs and Rangno, 1990).…”
Section: Introductionmentioning
confidence: 99%